THE CORRELATION BETWEEN DRAW LABEL CAPTION (DLC) AND DRILL TECHNIQUE TOWARD ENGLISH WRITING ABILITY - Fitri Palupi Kusumawati (Universitas Ahmad Dahlan)
Writing ability is one of the important parts that should be learnt in the school. Writing can be said that it is very important for the students, because the students can express their ideas and cxperience in writing form. The teachers should always look for which one suitable technique to be applied to the students, in order to make the students interested in learning writing, they are Draw-Label-Caption (DLC) and Drill Technique. In this research, the researcher will compares DLC and Drill techniques that are the most effective technique to improve the students’ writing ability.In this experimental research, there are 3 variables. That are 1). Draw-Label-Caption (DLC) technique as the first independent variable. 2). Drill technique as the second independent variable. 3) Writing skill as the dependent variable. The method that is used in this research is test. Students are asked to write the text in English based on predetermined theme. In this study, researcher uses pre-test and post-test. Based on the data analysis the researcher gets the result of Based on the calculation, it is found that: 1) Fratio = 7,5 and Ftable at significance level 1% is 7,08 and at significance 5% is 4,00. At this point the researcher finds that Fratio is bigger than Ftable. The researcher concludes that there is difference of students’ English writing ability through DLC and Drill technique. 2) Fratio = 37,7 at the same signifficance level. So there is difference of students’ English writing ability through DLC and Drill technique.